(untitled) (Scientific journal of the Fergana State University, 2025)
The article presents the introduction of innovative ussus aimed at the physical development of students in the process of physical education training, as well as experimental results, and analyzes the indicators of anthropometric, physical development of students-young people. During the experiment, the physical development of boys and girls was thoroughly studied in experimental and control groups.